PELATIHAN DETEKSI BAHAN PEMUTIH HIDROKUINON PADA KOSMETIK MENGGUNAKAN SPEKTROFOTOMETER UV-VIS PADA SISWA SMK FARMASI DI KOTA BEKASI - Intan Kurnia Putri; Melania Perwitasari; Reza Anindita; Maya Uzia Beandrade (Jurnal Abdi Insani, 2026)
The Ultra Violet Visible (UV-Vis) spectrophotometer for examining hydroquinone in whitening creams needs to be introduced to Pharmacy Vocational High School students. Therefore, it is necessary to carry out community service activities (CSA) in the form of training for Pharmacy Vocational High School students in Bekasi City in the form of training in the detection of whitening cream using a UV-Vis spectrophotometer. The purpose of this CSA activity is to provide knowledge and skills regarding the procedure for examining hydroquinone in whitening creams using a UV-Vis spectrophotometer. Furthermore, this PKM also aims to introduce the application of UV-Vis spectrophotometers in the field of pharmaceutical chemistry. The CSA method includes planning by offering school-integrated CSA programs to several Pharmacy Vocational Schools in Bekasi City and sending activity flyers via WhatsApp. The implementation phase was carried out by administering a pre-test, presenting material, practicing using a UV-Vis spectrophotometer, and administering a post-test. The evaluation stage is carried out by processing qualitative and quantitative data. The results of this CSA included 59 PKM activity participants at Pharmacy Vocational Schools; from statistical analysis using the t-test, there was a significant difference (P <0.05) in the average value of the understanding level of Pharmacy Vocational High School students after being given training UV-Vis spectrophotometry. As for the 15 products examined, eight products contained hydroquinone, which consisted of 6 products containing more than 2% while 1 product contained less than 2%. This CSA concludes that providing UV-Vis spectrophotometry materials and training as a CSA package can increase their understanding and enthusiasm for their interest in the UV-Vis spectrophotometer as an instrument for detecting harmful substances in cosmetics.